Efficacy and safety of belimumab therapy in lupus nephritis: a systematic review and meta-analysis - Han Zhang; Juan Chen; Ying Zhang; Na Zhao; Dongmei Xu (Renal Failure, 2023)
Background Belimumab is the first biological agent approved for the treatment of systemic lupus erythematosus (SLE), but the efficacy of belimumab for lupus nephritis (LN) is not clear. We conducted this meta-analysis and systematic review to compare the efficacy and safety of belimumab with those of conventional therapy for LN.Methods PubMed, EMBASE, Cochrane Library, Clinical Trials.gov were searched in 31 December 2022 to identify relevant adult human studies reporting effectiveness outcomes of belimumab in patients with LN. Review manager (RevMan 5.4) was used for data analysis with fixed effects model based on heterogeneities.Results Six randomized controlled trials (RCTs) were included in the quantitative analysis. A total of 2960 participants were identified. Belimumab plus standard therapy significantly improved total renal response rates (RR, 1.31; 95% CI, 1.11–1.53; p = 0.001) and complete renal RRs (1.47; 95% CI, 1.07–2.02; p = 0.02) compared with the control plus standard therapy group. It significantly reduced the risk of renal flare (RR, 0.51; 95% CI, 0.37–0.69; p < 0.001) and renal function worsening or progression to end-stage renal disease (ESRD) (RR, 0.56; 95% CI, 0.40–0.79; p = 0.001). When assessed with the incidence of adverse events, no significant differences between the two groups were observed for the occurrence of treatment-related adverse events (RR, 1.04; 95% CI, 0.99–1.09; p = 0.12).Conclusions This meta-analysis showed that belimumab plus standard therapy was more effective and had a favorable safety in patients with LN.